Surgical intervention in aggressive ulcerative pyoderma gangrenosum - Maham Mudassir; Rabia Ali; Sikandar Saeed; Ali Rafique Mirza (Journal of the Pakistan Medical Association, 2022)
Pyoderma Gangrenosum (PG) is a rare, debilitating, and painful disease of the skin. Its aetiology and pathophysiology are not well understood. However, it is known that PG is not bacterial in origin, as previously believed. A significant number of cases of PG report a phenomenon called pathergy, which is characterized by the appearance of new lesions after the application of trauma to the skin. This represents a unique challenge for surgeons in cases that are refractory to medical therapy. The objective of this study is to review past literature and report a case of PG in a 19-year old woman, who presented with recurrence, after undergoing skin grafting one year back. The patient was referred for split thickness skin grafting (STSG) to reduce the psychological and physical morbidity as a result of this disease. Continuous...